Authenticating Hafu Identities on Instagram: A Small Stories Analysis of Interactions on Hafugods - Mark, Laura (Narrative Works, 2025)
Described as “the predominant narrative environment for contemporary storytellers” (Mäkelä & Meretoja, 2022), social media are attracting increasing attention as sites for the study of a wide range of everyday narrative practices. Moreover, storytelling has become integrated into platform architectures through features such as Stories on Instagram, Snapchat and Facebook, and is being celebrated as “the ideal vehicle for presenting an authentic self” (Georgakopoulou, 2022). The word authenticity finds its roots in the Greek authentikós, (autós, self) and is associated with notions such as realness, genuineness, credibility and truthfulness (Lacoste, Leimgruber & Breyer, 2014, p2). In interactional sociolinguistics, authenticity is treated as an effect of discursive performance and negotiation of identity between participants in an interaction. The analytical focus is therefore on the discursive strategies and interactional processes that authenticate a person’s claim to a particular identity or group membership. This chapter explores the implications of authenticity as discursive performance in relation to hafu (ハーフ) identities, through a Small Stories (Georgakopoulou, 2013; 2016) analysis of an Instagram account called hafugods. Hafu is a racialised identity term used to describe someone who is mixed-ethnic or mixed-race Japanese, and hafugods presents itself as a space for telling stories about what it means to be hafu. The analysis demonstrates how storytelling is being mobilised for the performance of hafu identities, and reveals how alignment strategies such as ‘ritual appreciation’ and ‘knowing participation’ (Georgakopoulou, 2016) serve as authenticating practices of proving membership to the group, and by extension, a hafu identity.